Modern Method to Compute the Determinants of Matrices of Order 3 - Ahmed, Ali A.M.; Bondar, K. L. (Journal of Informatics and Mathematical Sciences, 2014)
In this paper we present new method to compute the determinants of 3 × 3 matrices. This method gives an easy schemes to compute the determinants of 3 × 3 matrices. It also gives fast approximation as we described only five elements of the determinant. This new method creates opportunities to find other new method to compute the determinants of higher orders, also.